An analysis of public distribution system in Jaunpur district, Uttar Pradesh - Atul Kumar Singh (National Geographical Journal of India, 2022)
The Public Distribution System is an Indian food security system established under the Ministry of Consumer Affairs, Food and Public Distribution. It evolves a system of management of scarcity through the distribution of food grains at affordable prices and is operated under the joint responsibility of the Central and the State Governments. The government of India promoted Public Distribution System for extending basic necessary goods at subsidized rates. But their primary motto has not been fullled due to numerous problems prevailing in the operation and function of PDS. Thus, an attempt has been made to ascertain the problems prevailing in PDS taking a case of the Jaunpur district of Uttar Pradesh. Garrett's Ranking Technique has been used to analyze the problems faced and solution given by consumers at Fair Price Shops from the primary survey. The result of the study indicates that compulsion to buy unwanted grocery goods (72.84 per cent) is the main problem followed by unable to obtain free items(72.75 per cent), poor quality of goods (70.13 per cent), adulteration (69.85 per cent), less weighed(69.46 per cent ), irregular supply (69.43 per cent), overcrowding (68.21 per cent), inconvenient working time (67.44 per cent ) and the like are the common problems found in the function of Public distribution system and to resolve these problems certain preferred solutions, as well as suggestions mainly to use token system (73.48 per cent), Payment for fair price shopkeepers (73.10 per cent), To lter real beneciaries (72.56 per cent ), Notice board information (71.48 per cent), One ration card one electric connection rule (71.03 per cent) and the like are the common solutions have been given by respondents in the study area.